Protección del desarrollo de productos elaborados en la carrera de Agroindustria a través del secreto industrial de (jamón de paiche, mortadela de cachama y salchicha de tilapia). - Peñaherrera Madril, Pablo André (2021)
The intellectual property registered in Ecuador, such as patents and industrial secrets related to academia are extremely alarming, since, for legal reasons, educational institutions prefer to register them in other countries. This research as an integrating project was carried out with the objective of registering the industrial secret products made at the Agroindustry Mayor in Technical University of Cotopaxi. The registry of three industrial secrets corresponding to different sausages was carried out: Paiche ham, Cachama mortadella and Tilapia sausage. Information was collected from previously submitted degree projects, the necessary documentation was prepared for notarizations and the registration was carried out as an industrial secret. The actions carried out were under the supervision of the tutor, staff of the career pilot, the legal department of the University, SENADI technicians and a legal study. The registration of the industrial secret as intellectual property in the National Service of Intellectual Rights (SENADI), will help significantly with the fulfillment of the PEDI 2021 - 2024 as well as in the fulfillment of the quality standards demanded by the Quality Assurance Council of Higher Education (CACES).